Enterobacteriaceae and pseudomonadaceae on the dorsum of the human tongue - Conti, Simone (2009)
Objective: The aim of this study was to correlate the presence of Enterobacteriaceae, Pseudomonadaceae, Moraxellaceae and Xanthomonadaceae on the posterior dorsum of the human tongue with the presence of tongue coating, gender, age, smoking habit and denture use. Material and Methods: Bacteria were isolated from the posterior tongue dorsum of 100 individuals in MacConkey agar medium and were identified by the API 20E system (Biolab-Merieux). Results: 43% of the individuals, presented the target microorganisms on the tongue dorsum, with greater prevalence among individuals between 40 and 50 years of age (p=0.001) and non-smokers (p=0.0485). Conclusions: A higher prevalence of Enterobacteriaceae and Pseudomonadaceae was observed on the tongue dorsum of the individuals evaluated. There was no correlation between these species and the presence and thickness of tongue coating, gender and presence of dentures.